BENTUK PENYERTAAN TINDAK PIDANA KEKERASAN OLEH ANAK YANG MENGAKIBATKAN LUKA BERAT DAN KEMATIAN: Form of Inclusion of Violent Crimes by Children Causing Serious Injury and Death - Mahirah,, Rifqa; Syahputra, Azmi (Faculty of Law, Universitas Trisakti, 2024)
Children are the successors of the nation who will later make changes which are when they are in the womb until they are 18 years old. At this time there are many children who carry out criminal acts, for example violence as contained in decision No. 18/Pid.Sus-Anak/2022/PN Jkt.Brt which in this case the children used acts of violence simultaneously in the form of stabbing and kicking the victims which resulted in the victims suffering serious injuries and death. This writing uses the literature study method, this type of research is normative, this research is descriptive analysis in nature, and in drawing conclusions using deductive logic. The children's actions have met the qualifications of the articles charged against them and there are specific inclusions in Article 76C of Law no. 35 of 2014 concerning child protection, which is only specifically for each person to apply violence against children.